ETHNOMATHEMATICS EXPLORATION: NUMBER PATTERNS IN BAMBOO WOVEN CRAFTS IN TULUNGAGUNG - Elly Susanti; Rizqita Alimatun Nisa’; Mohammad Nadzir Azhari; Marhayati Marhayati (IAIN Ambon, 2020)
Woven craft when viewed from its form will form a regular and even repetitive patterns, so that it contains mathematical concepts. The mathematical concepts that exist in woven crafts are number patterns. Number pattern is a number that has certain rules that will form a regular sequence of numbers. This study aims to determine the pattern of numbers in woven crafts in Tulungagung Regency, especially in Sepatan Village, Gondang Regency. This study uses a qualitative approach to the type of ethnographic study. Data collection techniques in this study are the study of literature, observation, interviews, documentation, and field notes (field notes). The results showed that there were three number patterns in the process of making a solid. First, if the process of making an area starts from K1 B1 the number pattern formed is 1-1-2-3-1-1-2-3. Secondly, if the process of making an appearance starts from K3 B2 the pattern formed is 3-1-1-2-3-1-1-2. Third, if the process of making an area starts from K1 B3 the number pattern formed is 2-3-1-1-2-3-1-1. While the number patterns that are formed in the making process besek there are three patterns that are the first if the manufacturing process starts from K1 B1 the pattern formed is 2-3-1-1-3-2-1-1-3-2-1-1-2 -3-1-1. The two patterns that are formed when the manufacturing process starts from K2 B5 are 3-2-2-4-3-2-4-2-2-3. The three patterns that are formed when the manufacturing process starts from K4 B8 are 1-1-3-1-2-3-1-1-2 Secondly, if the process of making an appearance starts from K3 B2 the pattern formed is 3-1-1-2-3-1-1-2. Third, if the process of making an area starts from K1 B3 the number pattern formed is 2-3-1-1-2-3-1-1 etc. Keywords: Exploration, Ethnomatematics, Number Pattern, Woven Bamboo